Warming simulation for autoclaved aerated concrete structures at fire conditions - Nguen Тхань; Kudryashov Вадим; Drobysh Антон (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2016)
Purpose. The paper is devoted to experimental study data of autoclaved aerated concrete warming simulation at fire conditions. Methods. The specimens of autoclaved aerated concrete were heated in flaming machine and muffle furnace. Full-scale fire experiment was planned and conducted. The results of experiments were discussed. Findings. The autoclaved aerated concrete structures have low thermal conductivity and high shrinkage rate at fire. The behavior and finite-element model for local destruction of autoclaved aerated concrete walls with steel stiffening elements was obtained. It is not recommended to use steel stiffening for fire walls and partitions. Application field of research. The obtained experimental study data could be used in fire resistance design of autoclaved aerated concrete structures. Conclusions. Fire resistance design of autoclaved aerated concrete structures should include heating study jointed with shrinkage rate, as far as adjacent elements behavior at fire.